Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Anthropology
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI; Bronislaw; 1884-1942; POLANYI; Karl; 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

Markets in West Africa: Karl Polanyi, or what sort of social formation - Saul, Mahir (Market as Place and Space of Economic Exchange: Perspectives from Archaeology and Anthropology, 2018)
Anthropology
Keywords: West Africa; disembeddedness; economic anthropology; economic history; markets

La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
History; Anthropology; Economics
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences